Differential Activation of TRPM8 by the Stereoisomers of Menthol - Chen, Xiaoying; Xu, Lizhen; Zhang, Heng; Wen, Han; Yang, Fan (Frontiers in Pharmacology, 2022)
The stereoisomers of menthol elicit cooling sensation to various levels. Though the high-resolution three-dimensional structures of the menthol receptor, the transient receptor potential melastatin 8 (TRPM8) ion channels, have been revolved in different states, the menthol-bound state structure is not determined and how the stereoisomers of menthol interact TRPM8 remains largely elusive. Taking advantage of the identical atom composition but distinct spatial orientation of chemical groups in menthol stereoisomers, we performed thermodynamic mutant cycle analysis (TMCA) with patch-clamp recordings to probe the interaction between these ligands and TRPM8. By comparing (-)-menthol with (+)-neoisomenthol or (+)-neomenthol, we observed that the isopropyl or hydroxyl group in menthol interacts with the S4 or S3 helix in TRPM8, respectively. These interactions were also corroborated in our molecular docking of the stereoisomers, though the predicted structural details in the interactions of these ligands with TRPM8 residues are different. Therefore, we suggest similar molecular mechanisms of TRPM8 activation by the stereoisomers of menthol, while the binding configuration of an individual stereoisomer is varied.